2018
DOI: 10.2478/jce-2018-0017
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Acute Inflammatory Response and Infarct Size in Stemi Patients Undergoing Primary PCI

Abstract: Background: The inflammatory response of the immune system plays a major role in the period following an acute myocardial infarction (MI), as it coordinates the formation of the fibrous scar tissue that replaces the infarcted myocardial cells and ultimately leads to healing and remodeling of the affected zone. Along with other pro- and anti-inflammatory cytokines and acute phase proteins, interleukin-6 (IL-6) and C-reactive protein (CRP) are associated with the extent of the infarct size (IS) and may serve as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…The pro‐inflammatory phase occurs in the first 3 days after the infarction, is characterised by higher levels of circulating pro‐inflammatory cytokines and acute phase proteins such as IL‐6 and CRP and is associated with the immediate complications occurring early after the acute coronary event. The pro‐reparatory phase starts after 1–2 days and is responsible for cell accumulation at the site of the infarcted tissue in order to repair the damaged myocardium …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pro‐inflammatory phase occurs in the first 3 days after the infarction, is characterised by higher levels of circulating pro‐inflammatory cytokines and acute phase proteins such as IL‐6 and CRP and is associated with the immediate complications occurring early after the acute coronary event. The pro‐reparatory phase starts after 1–2 days and is responsible for cell accumulation at the site of the infarcted tissue in order to repair the damaged myocardium …”
Section: Discussionmentioning
confidence: 99%
“…The pro-reparatory phase starts after 1-2 days and is responsible for cell accumulation at the site of the infarcted tissue in order to repair the damaged myocardium. 19,20 Malnutrition has emerged as another important player in this equation of inflammation-atherosclerosis interaction and may represent a risk factor and/or prognostic indicator of cardiac outcomes. 13 Another study showed that, in STEMI patients, the long-term risk of all-cause death was higher in patients with malnutrition, expressed by a CONUT score <3.…”
Section: Discussionmentioning
confidence: 99%
“…DOI: 10.1159/000506176 senting with ST-elevation myocardial infarction (STEMI) is well known. In patients with STEMI treated with primary percutaneous coronary intervention (PCI), higher baseline CRP levels are associated with larger infarct size, transmural extent, and poor systolic and diastolic function of left ventricle (LV) and independently predicted 30-day mortality [2][3][4]. CRP-apheresis following STEMI is feasible, safe, and results presented from a small cohort showed significant beneficial effects of CRP both on myocardial infarction size and wall motion [4].…”
Section: Introductionmentioning
confidence: 99%
“…CRP-apheresis following STEMI is feasible, safe, and results presented from a small cohort showed significant beneficial effects of CRP both on myocardial infarction size and wall motion [4]. Therefore, CRP reduction from plasma brings selective CRP-apheresis as innovative therapeutic approach in the treatment of AMI [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the study by Morariu et al show us how the inflammatory reactions in acute settings can impact the cardiac status on a medium and potentially long term, providing an explanation for the findings we commonly see at the routine, image-based follow-up of patients suffering an acute cardiac event. 17…”
mentioning
confidence: 99%